การศึกษาการจัดกิจกรรมเสริมหลักสูตรดนตรีไทย ในโรงเรียนมัธยมศึกษา สังกัดกรมสามัญศึกษา : กรณีศึกษาโรงเรียนที่ได้รับรางวัลการประกวดวงดนตรีไทยถ้วยพระราชทาน สมเด็จพระเทพรัตนราชสุดาฯ สยามบรมราชกุมารี - สายพิณ พุทธิสาร (จุฬาลงกรณ์มหาวิทยาลัย, 2000)
The purpose of this research was to study the activity organization and the problems of Thai classical music co-curricular activities in the secondary schools holding Her Royal Highness Princess Sirinthorn s Cup Award in Thai classical music band. The population were eight secondary schools under the Department of General Education awarded in Thai classical music band in 1995 to 1999. The obtained data were from administrators, art education head teachers, activity advisory teachers and students participated in such activities. Research instruments were consisted of semi-structured interview form, observation form and document study form. The data were statisticaly analyzed by means of content analysis method and presented in table with description. The analytical result showed that the activities were organized with the operational plans and project. The projects were drawn by activity advisory teachers with the coordination provided for the facilitation of the buildings and sites. The special experts as well as alumni were invited to join the activities with the budget provided for the activity organization obtained from the educational supports and from the Parents and Teachers Association. The membership application was publicized by the activity advisory teachers to students in classrooms. Most participating students were having talents in the field of Thai classical music, however, the problems found in the activity organization were dealing with the unsuitability of the practicing places, the shortage of the experts and the lack of budget. For the activity organization, the members orientation was available, for the organized committee consisting of the appointed teachers committee and elected students committee was conducted for the mutual activity organization planning. The activities conducted for students were the practicing activities for the contest, joining for the school activities, community service activities, all these were done after the school hours in the evening and in the morning beforethe flag salutation for the practicing which the activity organization approach was intended for the promotion of dexterity, ability development, skill enhancement and the creation of the opportunity for further study. The natures of practice were for individual skill practicing and band practicing. The activity advisory teachers took good care of the activity organization which was monitored closely by the administrators through the performance reports of the activity organization and the visitation to provide them the morale and will power. Nevertheless, the problem was the insufficient time of practice. For the evaluation of the activity organization, the activity advisory teachers, in cooperation with students, discussed and prepared the documentary report of the activity organization performance when all the activities were over. The problems of the activity organization evaluation were, was no written activity organization evaluation performance recording, the tardiness and inconsistency of the activityorganization performance reporting